PERAN JAKSA PENUNTUT UMUM DALAM PROSES DIVERSI TERHADAP ANAK BERHADAPAN DENGAN HUKUM (Studi Kasus No. 8/Pid.Sus-Anak/2015/PN.Sda) - Wanda Meidina Akhmad; Haniyah Haniyah (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2023)
Prosecutors are Functional officials who are authorized by the Act to conduct prosecutions. In the Law of the Republic of Indonesia Number 11 of 2012 concerning the Juvenile Criminal Justice System, that at every level of diversion is sought for diversion, the concept of diversion is the transfer of the settlement of children's cases from the criminal justice process to processes outside the criminal justice system. The application of the concept of diversion has an influence on the role of the prosecutor in performing and carrying out his duties. Attorney General Regulation No. 006/A/J.A/2015 on diversion guidelines at the prosecution level requires law enforcement officials, especially the Public Prosecutor, to handle children's cases using a restorative justice approach and seeking d iversion. Similarly kasus No. 8/Pid.Sus-Anak/2015/PN. Natural resources need to carry out a diversion process, the purpose of this study is to make the public understand more, about diversion of cases of children facing the law, because so far there are many cases of children facing the law, who do not use diversion in solving children's cases. The research methods used by normative juridical and empirical approaches, based on the results of research at the Sidoarjo District Attorney's Office regarding the diversion process are not fully in accordance with the provisions of the law, but have attached importance to the principle of best interests for children.